Navigating Conditional Funding: Policy Reforms and Transparency Challenges in Indonesia’s JETP Implementation - Maudy Noor Fadhlia; Ahmad Mujaddid Fachrurreza; Zhillan Fahlevi (UIN Sunan Gunung Djati Bandung, 2026)
Indonesia, which possesses significant renewable energy potential, is at a critical stage in its energy transition. Through the Just Energy Transition Partnership (JETP), the country has secured an international financing commitment of USD 20 billion. However, access to these funds depends on meeting several requirements related to policy reform, transparency, and clear implementation strategies. This study aims to examine the challenges faced by Indonesia in fulfilling these requirements and to analyze the relationship between global climate finance expectations and Indonesia’s domestic socio-economic and political dynamics. This research employs a qualitative case study approach based on document analysis of the JETP agreement, government policies, and reports from international organizations and civil society groups. The findings indicate that although Indonesia demonstrates strong commitment to energy transition, policy reforms frequently encounter resistance from existing regulatory frameworks and entrenched interests within the fossil fuel sector. In addition, limited transparency in project selection and weak inter-institutional coordination continue to constrain effective fund utilization. These findings suggest that the success of JETP implementation depends not only on financial absorption capacity but also on strengthened governance, regulatory consistency, and transparent implementation frameworks.